2015
DOI: 10.2147/tcrm.s79238
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvements in decreasing medication administration errors made by nursing staff in an academic medical center hospital: a trend analysis during the journey to Joint Commission International accreditation and in the post-accreditation era

Abstract: BackgroundMedication errors may occur during prescribing, transcribing, prescription auditing, preparing, dispensing, administration, and monitoring. Medication administration errors (MAEs) are those that actually reach patients and remain a threat to patient safety. The Joint Commission International (JCI) advocates medication error prevention, but experience in reducing MAEs during the period of before and after JCI accreditation has not been reported.MethodsAn intervention study, aimed at reducing MAEs in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 19 publications
0
13
0
4
Order By: Relevance
“…That is to say that these are actions that were reported in the literature that were taken as a result of an event. In regards to action, the major areas were documentation [ 10 , 32 , 37 , 41 , 46 , 56 , 58 ], implementation [ 10 , 32 , 37 , 58 ], and culture [ 10 , 29 , 41 , 53 , 58 ] relative to the use of health IT.…”
Section: Resultsmentioning
confidence: 99%
“…That is to say that these are actions that were reported in the literature that were taken as a result of an event. In regards to action, the major areas were documentation [ 10 , 32 , 37 , 41 , 46 , 56 , 58 ], implementation [ 10 , 32 , 37 , 58 ], and culture [ 10 , 29 , 41 , 53 , 58 ] relative to the use of health IT.…”
Section: Resultsmentioning
confidence: 99%
“…Dentre os tipos de erros na AM encontrados nesta revisão, o principal deles diz respeito à dosagem medicamentosa, presente em 27 estudos (67,5%) (8,(10)(11)(13)(14)(16)(17)(19)(20)(23)(24)(25)(26)(27)(28)(30)(31)(32)34,36,(42)(43)(44)(45)(46)(47)(48)(49) . Corroborando com tal achado, uma pesquisa (50) que teve como um dos objetivos identificar o perfil dos erros cometidos durante o preparo, encontrou que 67,7% dos erros estavam associados a doses preparadas erroneamente.…”
Section: Discussionunclassified
“…Esta realidade também foi encontrada na presente pesquisa, em que a administração da medicação errada foi o segundo erro mais comum entre os estudos analisados e esteve presente em 62,5% (n=25) (8)(9)(10)(11)13,16,(20)(21)(23)(24)(25)(26)(28)(29)(30)(31)(36)(37)(42)(43)(45)(46)(48)(49)53) da amostra, seguido pelo medicamento administrado ao paciente errado (n=21;52,5%) (8)(9)(10)(11)16,18,22,(23)(24)(25)(26)(27)(28)(30)(31)(33)(34)(36)(37)(46)(47) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Since January 2013, SAHZU has required that two licensed health care professionals must perform a standardized independent double-check prior to barcode-assisted medication administration of narcotics, insulin infusion, chemotherapeutic drugs, and intravenous heparin. 30 On-site inspection results and retrospective review of nursing record system showed a 100% implementation rate. Morriss et al 31 reported that patients who were treated with an opioid in the absence of a barcode-assisted medication administration system had a 10% probability of an adverse drug event.…”
Section: Standardized Administration and Monitoringmentioning
confidence: 99%